MUHAMMADIYAH RENEWAL IN THE FRAME OF ISLAMIC EDUCATION AND SOCIAL CHANGE - Sabila, Ana Maulida; Nurhakim, Nurhakim; Romelah, Romelah (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2023)
Muhammadiyah is one of the largest Islamic organizations in Indonesia that has the character of tajdid (renewal) and has made a real contribution through its charity to the nation and state. This includes renewal in the field of education and social religion. This paper discusses the history of the birth of Muhammadiyah, the renewal of Muhammadiyah Islamic Education, and the role of Muhammadiyah in responding to social changes in society. The research method used is descriptive analysis. The results showed that: 1) Muhammadiyah was born as a response to the damage to the faith, the backwardness of the people, as well as the development of Islamic thought in the Middle East which required a change, one of which was in the field of education. 2) The effort to reform Islamic education by KH Ahmad Dahlan was carried out by unifying the colonial education system with the traditional education system that existed at that time. 3) Muhammadiyah's renewal as a response to social change was realized through its business charities. Entering the second-century Muhammadiyah is faced with challenges and contemporary issues of the postmodern period which certainly requires Muhammadiyah to continue to improve.